ANALISIS SURAT AL-KAHFI AYAT 60-82 TENTANG KONSEP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Siti Lailiyah; Muhammad Saefullah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
The purpose of this study was to determine the learning concept of Islamic Education contained in Surat al-Kahf verses 60-82 and know the values ​​of learning contained in the Qur'an Al-Kahf verses 60-82. In this study researchers used a purely descriptive qualitative type of research on the grounds that the information used in this study is not in the form of numbers but in the form of data from books, journals, magazines, or newspapers, all of which will be described clearly and in detail to develop theory of Islamic education. In qualitative descriptive research here, the researcher uses the research library method, which is a library research. The results of the study showed that the learning concepts contained in the learning between the prophet Moses and the prophet Khidir were more on the method of discussion, reality-based problem solving. In this story, the prophet Moses was asked to critically understand the phenomenon that had just issued a statement, not to blame right away. But what happened to the prophet Moses was too early to conclude that what was done by the prophet Khidir was wrong. This does not mean it is forbidden to ask questions, but rather the prophet Moses was asked to read the process as a whole, not asking directly. This is one of the active learning learning strategies.